Optimizing Bionic Prosthetic Finger 3D Topology Design and Comprehensive Testing of Fully Compliant Mechanisms - Sollapur, Shrishail B; Dakhole, Mangesh Y; Suryawanshi, Shubham R; Vijay Kumar, Dr Vishnu; Abu Bakar, Suriani (International Journal of Integrated Engineering, 2024)
Compliant mechanisms, with their cohesive structure and adaptable motion, are well-suited for creating prosthetic digits that closely mimic the functionality of human fingers. However, designing flexible prosthetic fingers is challenging because traditional assumptions based on rigid-link systems do not translate well. This study presents an innovative 3D structure optimization approach for designing prosthetic fingers that are compatible with biological systems. The suggested method, carried out in MATLAB, allows for quick production of these fingers through the use of selective laser sintering technology. A design example is presented, utilizing load testing and finite element simulations to effectively validate the realized finger’s bending capability, clarifying the framework’s implementation. The refined fingers demonstrate promising potential for integration into prosthetic hands in future endeavors, enabling intricate, gripping actions akin to the human hand.